Developing Small-Molecule Inhibitors of Protein-Protein Interactions Involved in Viral Entry as Potential Antivirals for COVID-19 - Buchwald, Peter (Frontiers in Drug Discovery, 2022)
Blocking protein-protein interactions (PPIs) involved in the initiation of the cell attachment and entry of viruses is an important antiviral mechanism of action including for neutralizing antibodies. Doing it with small-molecule inhibitors (SMIs) is challenging, as it is for all other PPIs, and might require the exploration of chemical space beyond that of typical drug-like structures. However, it could lead to new antiviral agents suitable for oral administration and acting on alternative targets, considerations that are essential for the development of widely acceptable and broad-spectrum preventive or curative therapeutics. Fostemsavir, an antiretroviral that acts via blocking of the gp120-CD4 PPI, supports the feasibility of the concept. Here, a brief review of relevant drug design considerations is presented together with a summary of the progress made toward the identification of SMIs targeting the PPI between the SARS-CoV-2 spike protein and ACE2 that initiates the viral attachment and cellular entry of this coronavirus causing the COVID-19 pandemic. SMIs identified in various screening assays that were also confirmed to have antiviral activity in a live virus or pseudovirus assay with an IC50<30 µM so far include several organic dyes (methylene blue, Evans blue, Congo red, direct violet 1), verteporfin, DRI-C23041, and cannabigerolic and cannabidiolic acids. While specificity and activity profiles still need improvement, results so far already provide proof-of-principle evidence for the feasibility of SMIs targeting the SARS-CoV-2-S–hACE2 PPI. Methylene blue, which is approved for clinical use, is orally bioactive, and could act by multiple mechanisms of action might have potential for repurposing for COVID-19 prevention and treatment.